Biological characterization, sequence type distribution and drug resistance profiling of Mycoplasma hyorhinis field isolates from pigs in Chongqing, China - Li, Huiying; Lian, Xiuwu; Li, Yilin; Jin, Ruiyan; Ma, Yunchong; Zhao, Ming; Wu, Yue; Yi, Dongsheng; Hu, Haixia; Yang, Yujiao; Ding, Honglei (Frontiers in Veterinary Science, 2026)
Mycoplasma hyorhinis is a ubiquitous pathogen of swine that causes polyserositis and polyarthritis and is also associated with conjunctivitis, meningitis, pneumonia, and abortions. This microorganism is a high prevalence pathogen in Chinese swine herds. However, few studies on M. hyorhinis have been reported in Chongqing, China. The overuse of antimicrobials has led to an increased risk of antimicrobial resistance, but a series of Chinese herbal monomers exhibited antibacterial activity to drug-resistant bacteria, including mycoplasmas. The aim of the study was to determine the prevalence, sequence types, growth kinetics, susceptibility to antimicrobials and Chinese herbal monomers, and relationships between the phenotypes and genotypes in terms of the resistance of M. hyorhinis to fluoroquinolones, macrolides and lincomycin. A total of 28 M. hyorhinis strains were recovered from the lungs of 404 slaughtered pigs. The isolates belonging to 11 novel STs, ST226, ST227, ST228, ST229, ST230, ST260, ST261, ST262, ST263, ST264 and ST265, were clustered separately from other reference isolates in the database. The growth kinetic of each isolate was generated, and the maximum color changing unit (CCU) values of isolates varied from 1012 to 1020 CCU/ml. In vitro susceptibility testing showed that the isolates were inhibited by low concentrations of tiamulin (MIC: ≤ 0.25 μg/ml), doxycycline (MIC: ≤ 0.25–1 μg/ml), ciprofloxacin (MIC: ≤ 0.25–2 μg/ml), florfenicol (MIC: 0.5–2 μg/ml), kanamycin (MIC: ≤ 0.25–4 μg/ml), enrofloxacin (MIC: 0.5–4 μg/ml) and berberine hydrochloride (MIC range: 1–8 μg/ml). However, the MICs of erythromycin were high (MIC: 32–≥128 μg/ml) for all isolates. The MICs of tylosin, tilmicosin and lincomycin for 50%, 60.7% and 46.4% of isolates were equal to or >16, 32 and 8 μg/ml, respectively. No correlation was detected between resistance to fluoroquinolones and QRDRs. However, the high MICs of tylosin, tilmicosin and lincomycin were most likely attributed to an A1553G mutation in domain V of the 23S rRNA. Our findings demonstrated the diversity of STs among M. hyorhinis isolates in Chongqing. The high MICs of M. hyorhinis isolates to macrolides and lincomycin suggested that the use of lincomycin for the treatment of M. hyorhinis infections should be carefully evaluated.